Design and simulation of fuzzy controller for three phase grid connected PV systems - Youssef, Ayman; El-Telbany, Mohammed; Zekry, Abdelhalim (International Journal of Engineering and Technology, 2019)
this paper presents a design, complete simulation and hardware implementation of three phase grid connected inverter. The proposed scheme is fuzzy logic current control to control the current through the PV inverter switches. The inverter control system algorithms are developed and simulated in MATLAB/SIMULINK. A 9.1 Kw system is implemented and tested in MATLAB/SIMULINK. The proposed scheme achieves low harmonic distortion. A comparison between the fuzzy logic controller and other classical controllers proposed in literature is given. the controller is implemented on Arduino and a complete system is built on hardware. results show the superior performance of the fuzzy logic controller.Â